2012
DOI: 10.1115/1.4006377
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Low Temperature Diesel Combustion Sensitivity to Engine Operating Parameters

Abstract: This work elucidated which engine operating parameters have the greatest influence on Low temperature diesel combustion (LTC) and emissions. Key parameters were selected and evaluated at low and intermediate speed and load conditions using fractional factorial and Taguchi orthogonal experimental designs. The variations investigated were: about ± 5% in EGR rate, fuel injection quantity and engine speed respectively; and ± we in intake charge temperature. The half-fractional factorial results showed that the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…This is attributable to the larger amounts of oxygen present late in the combustion event, enabling oxidation of partial combustion products which again elucidates the role of in-cylinder oxygen concentrations on these emissions. This is consistent with an earlier publication [28] in which it was reported that oxygen concentration in the intake charge is the decisive parameter in the high-EGR LTC strategy and the THC and CO emissions show significant sensitivity to a minor change in the EGR rate at the intermediate load LTC operation.…”
Section: End Of Injection (Eoi)supporting
confidence: 93%
See 2 more Smart Citations
“…This is attributable to the larger amounts of oxygen present late in the combustion event, enabling oxidation of partial combustion products which again elucidates the role of in-cylinder oxygen concentrations on these emissions. This is consistent with an earlier publication [28] in which it was reported that oxygen concentration in the intake charge is the decisive parameter in the high-EGR LTC strategy and the THC and CO emissions show significant sensitivity to a minor change in the EGR rate at the intermediate load LTC operation.…”
Section: End Of Injection (Eoi)supporting
confidence: 93%
“…Note that in the present work higher levels of EGR was required to achieve low smoke emissions in the high boost pressure LTC cases, which is consistent with other work [18,19]. The trend in the flame luminosity is expected to be strongly dependent on intake charge dilution, since engine-out smoke emissions show significant sensitivity to the minor changes in the EGR rate at the intermediate load (16 mg/cycle fuelling quantity) LTC operating condition [28]. Therefore, the increased EGR levels at high intake pressure, as is the case in the present investigation, would impact the soot luminosity and its distribution inside the combustion chamber significantly.…”
Section: Assessment Of Low Smoke Low Nox High-egr Operating Conditionsupporting
confidence: 89%
See 1 more Smart Citation
“…With high-EGR LTC, even a small change in the EGR level can have a significant negative impact on the emissions, especially of PM. 20 As a result, the 40 cycles between 50% EGR and 60% EGR have an unfavourable intermediate EGR rate; this is significantly more complex than the 4 cycles observed for the increasing-load transient examined previously by Sarangi et al…”
Section: Modelling Of the Transients And Selection Of The Operating Cmentioning
confidence: 81%
“…With high-EGR LTC, even a small change in the EGR level can have a significant negative impact on the emissions, especially of PM. 20 As a result, the 40 cycles between 50% EGR and 60% EGR have an unfavourable intermediate EGR rate; this is significantly more complex than the 4 cycles observed for the increasing-load transient examined previously by Sarangi et al 14 Therefore, handling this decreasingload transient (conventional diesel to high-EGR LTC) is more complex than the increasing-load transient (high-EGR LTC to conventional diesel combustion).…”
Section: Modelling Of the Transients And Selection Of The Operating Conditionsmentioning
confidence: 90%